The Millennium Development Goals and communication for development: a study of Malawi and Zambia - Gomo, Tapiwa (My University, 2016)
The year 2000 witnessed a significant convergence of global policy positions. These positions range from the neoliberal regime which gained traction in the mid-1990s, participatory development models of the 1980s, and the technocratic approach to development of the late 1990s. Despite their ideological differences, these policy positions found co-existence in the (MDGs) and have framed how poverty is globally understood and how it should be addressed, including the use of communication especially the media to promote or fast track poverty reduction projects. This thesis is a critical analysis of the extent to which the United Nations (UN) Communication for Development strategy of 2007 has been used in Kamaila Village in Zambia and Mwandama Village in Malawi to implement MDG-related projects. The two villages were chosen because they have been exposed to different models of poverty reduction activities. The Mwandama Village project is part of the Millennium Village Project where a holistic approach is applied to address poverty, while the Kamaila Village is a beneficiary of a water project which is considered to be important to kick-start village-driven poverty reduction activities. Even though the two villages have been used as units of analysis, the main goal of this study was to examine the two policy documents as texts – the MDG and the UN Communication for strategy – how the discourse and narratives that inform them and their relationship with power, shape social practices and behaviour at national and village level. The study also sought to establish how language operates within the context of power relations by applying theories of global governance, knowledge and power, hegemony, participatory and media communication. The methodology used to gather data consists of a critical discourse analysis on the policy documents and qualitative interviews with different respondents from the villagers, the UN system, NGOs, media and governments. Through a combination of these theoretical frameworks and methodologies, this study has shown that the narratives and discourses that inform the MDGs are influenced by western actors who use the power of money to pursue their neoliberal interests under the guise of reducing poverty. The link between political power, the poverty reduction ideas and interests of elite actors saturates and remotely controls available policy spaces for participation with external knowledge and rules, starting from the UN system down to the villages thereby enabling neoliberal ideas to control the flow of knowledge and the construction of discourses. Despite attempts to harness local modes of social communication to transmit the neoliberal notions of poverty in the villages, individual villagers have discursively devised ways of maintaining their own ‘traditional’ ways of life. This highlights that poverty reduction discussions must not be too obsessed with controlling or changing people’s minds and behaviour but seek to understand the grassroots’ lifestyles as a baseline for informed intervention. Ignoring this baseline knowledge is one of the many reasons development has failed dismally since the 1950s because it is driven by capital interests from the top to bottom with less or no intentions to address poverty. In addition, the ability of media messages to influence practices and behaviour remains a contested arena. But as this study established, the strength of messages to alter social practices has its limitations because behaviour is a manifestation of several factors such as environment, context, biology, genealogy and culture, some of which are not linked to communication. However, communication within the context of the villagers is part of their way of exchanging or transmitting ideas and knowledge in producing and reproducing their culture and not to eliminate it. This thesis makes scholarly contribution through the use of a critical approach to international policy formulation, and participation within a globalised world. While several studies have analysed the link between communication and poverty reduction privileging the neoliberal construction of these themes, this study has demonstrated that the grassroots are not unthinking; they have a well-being, cultural context and communication ecology which needs to be understood first and respected. These findings expose the tensions between the neoliberal interests-driven elite view of poverty and the local way of viewing well-being.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Media Studies University of the Witwatersrand Johannesburg September 2015
Keywords: Communication in community development; Communication in economic development; Economic development--Zambia; Economic development--Malawi; Developing countries--Economic conditions--21st century